Reconceptualizing Islamic Education through al-Islam and Kemuhammadiyahan (AIK) for Advancing the SDGs in Indonesia - Mhd Lailan Arqam; Yogi Sopian Haris; Erik Tauvani Somae; Rahmadi Wibowo Suwarno (Universitas Muhammadiyah Surakarta, 2025)
Objective: This research aims to explain the urgency, reconceptualization, strategies, and implications of AIK transformation that support sustainable development. Theoretical framework: The theoretical framework of this research is based on Paulo Freire's Critical Pedagogy and Amin Abdullah's Integration-Interconnection paradigm. Literature review: AIK faces stagnation because it is still normative and less responsive to contemporary realities. Previous research has shown the potential for integration of Islamic values (tauḥīd, ʿubūdiyyah, itqān, iḥsān, imtiyāz, and khidmat) with SDGs indicators (SDG 1, SDG 4, SDG 10, SDG 13, SDG 16), and emphasizes the urgency of sustainability-based curriculum reform. Methods: This research method uses a qualitative approach based on a literature study, analyzing the content of the literature, identifying key themes that link Islamic values and SDGs indicators, and reconstructing the AIK paradigm from a sustainability perspective. Results: The results show that the AIK curriculum can be transformed into a contextual and transformative education model through the integration of Islamic values such as tauḥīd, ‘ubūdiyyah, itqān, iḥsān, imtiyāz, and perkhidmatan (service into the SDGs) indicators, including SDG 1 (No Poverty), SDG 4 (Quality Education), SDG 10 (Reduced Inequalities), SDG 13 (Climate Action), and SDG 16 (Peace and Justice). Its implementation includes curriculum renewal, cross-disciplinary collaboration, participatory learning, student research and social action, as well as critical pedagogy-based faculty training. Implications: The implications of AIK extend to the philosophical, curricular, cultural, and structural realms in Islamic higher education. Novelty: The novelty of this research lies in the integration of progressive Islamic values with SDG principles within a conceptual framework that has not been extensively explored, as well as the development of an AIK curriculum model that is responsive to global challenges in spiritual, social, and ecological aspects.